Mediators between body mass index and atrial fibrillation: a Mendelian randomization study - Gao, Ziting; Wei, Hongye; Xiao, Jun; Huang, Wuqing (Frontiers in Nutrition, 2024)
Background: Although obesity is a recognized risk factor of atrial fibrillation (AF), the mechanisms are not fully understood.Objective: We aimed to identify the potential mediators between body mass index (BMI) and AF.Methods: We conducted a two-sample Mendelian randomization (MR) analysis using publicly available summary-level data from genome-wide association studies. Univariable MR analyses were applied to identify potential mediators, and then the multivariable MR analyses were conducted to explore the mediated roles of circulating biomarkers, metabolic markers and comorbidities in the association between BMI and AF.Results: This MR study found a significant causal association between BMI and AF (OR=1.41, 95%CI=1.33-1.50; P<0.001), which was attenuated to 1.21 (95%CI=1.03-1.43) after being adjusted for leptin, in which 48.78% excess risk was mediated. After further adjustment for leptin and some cormorbidies, the association was attenuated to null (adjusted for leptin and sleep apnoea: OR=1.05, 95%CI=0.85-1.30; adjusted for leptin and coronary heart disease: OR=1.08, 95%CI=0.90-1.30; adjusted for leptin and systolic blood pressure: OR = 1.11, 95%CI= 0.88-1.41), resulting in 87.80%, 80.49% and 73.17% excess risk being mediated, respectively. Conclusion: These results identified an important mediated role of leptin, particularly for individuals with sleep apnoea, coronary heart disease or hypertension, providing some clues for the underlying mechanisms behind the impact of obesity on AF risk.